Internalization of Riau Malay Culture in Developing the Morals of Madrasah Ibtidaiyah Students - Syahraini Tambak; Siti Humairoh; Muhammad Ali Noer; Mawardi Ahmad (UIN Siber Syekh Nurjati Cirebon, 2020)
Abstract This study aims to describe the internalization of Malay culture in developing the morals of madrasah ibtidaiyah students through the role of the teacher. This type of research is a case study, with interviews and observations used as data collection techniques. Researchers conducted interviews with teachers and principals of madrasah, as well as observing the learning process and madrasah activities for one year. Data were analyzed by reducing the results found, making presentations, and attracting new meanings based on the data found. The results of this study showed that the internalization of Riau Malay culture in developing the morals of students was done through giving advice; giving motivation; giving warning; providing understanding; giving example; communicating with parents; protecting and looking after students; giving training; providing assistance; approaching; controlling; inviting; using learning methods; imposing sanctions; and giving reward. This study concludes that the moral development of madrasah ibtidaiyah students can be done by internalizing Riau Malay culture in the learning process both at school and at home.Keywords: Malay culture, morals, madrasah students, learning process.Â AbstrakPenelitian ini bertujuan untuk mendeskripsikan internalisasi budaya melayu dalam mengembangkan moral siswa madrasah ibtidaiyah melalui peran guru. Jenis penelitian ini adalah studi kasus, dengan wawancara dan observasi dijadikan sebagai teknik pengumpulan data.Â Peneliti melakukan wawancara kepada guru dan kepala madrasah, serta melakukan observasi proses pembelajaran dan kegiatan madrasah selama satu tahun. Data dianalisis dengan melakukan reduksi terhadap hasil yang ditemukan, melakukan penyajian, dan menarik makna baru berdasarkan data yang ditemukan. Hasil penelitian ini menunjukkan bahwa internalisasi budaya Melayu Riau dalam membentuk moral (akhlak) siswa yaitu dengan memberikan nasihat; memotivasi; memberikan teguran; memahamkan; teladan; berkomunikasi dengan orang tua; mengayomi dan menjaga peserta didik; memberikan latihan; memberikan bantuan; melakukan pendekatan; mengontrol; mengajak; menggunakan metode pembelajaran; memberikan sanksi; dan memberikan reward. Penelitian ini menyimpulkan bahwa pengeembangan moral siswa madrasah ibtidaiyah dapat dilakukan dengan menginternalisasikan budaya Melayu Riau dalam proses pembelajaran, baik di sekolah maupun di rumah.Kata kunci: budaya melayu, akhlak, siswa madrasah, proses pembelajaran.